2015
DOI: 10.1159/000368487
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>hTERT, BICD1</i></b> and Chromosome 18 Polymorphisms Associated with Telomere Length Affect Kidney Allograft Function After Transplantation

Abstract: Background/Aims: It has been confirmed that telomere length (TL) correlates with chronological donor age and that telomere shortening is accelerated in allografts. The aim of this study was to analyse the associations between graft rs2735940 hTERT and rs2630578 BICD1 gene polymorphisms and rs7235755/rs2162440 chromosome 18 polymorphisms, relative TL and kidney function after transplantation. Methods: The study enrolled 119 Polish Caucasian kidney allograft recipients (64M/55F, mean age 47.3±14.0 years). The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The frequencies of rs2735940 hTERT gene and rs2630578 BICD1 gene polymorphisms, as well as rs7235755 within chromosome 18 polymorphisms, among the recipients and donors were consistent with the Hardy-Weinberg equilibrium. These results have been described elsewhere [9,12]. …”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…The frequencies of rs2735940 hTERT gene and rs2630578 BICD1 gene polymorphisms, as well as rs7235755 within chromosome 18 polymorphisms, among the recipients and donors were consistent with the Hardy-Weinberg equilibrium. These results have been described elsewhere [9,12]. …”
Section: Resultsmentioning
confidence: 61%
“…It is broadly known that among them, genetic factors are of great importance [9,12,23]. There are also many promising studies focused on linkage between immune response mediators and cell status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, this term has been replaced with chronic allograft dysfunction (CAD), which is a much broader definition of long-term transplanted kidney function impairment. The diagnosis of CAD is based on functional and morphological (biopsy confirmed) deterioration of renal allograft at least 3–6 months after transplantation, whereas diagnosis of CAN was based on tissue examination [2325]. Ferlicot et al studied 67 cases of CAN and 13 controls.…”
Section: Telomere Length Assessment In Kidney Allograftsmentioning
confidence: 99%
“…In the case of the rs7235755 chromosome 18 polymorphism AA genotype, significant correlations were found, but they differed depending on the time of material collection. Nevertheless, we showed that genetic factors also influence telomere length and must be considered in further studies [25]. …”
Section: Authors’ Own Research On Kidney Transplantationmentioning
confidence: 99%